2022
DOI: 10.1029/2021wr030456
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Dissolution Patterns in Rough Fractures

Abstract: Rock fractures are ubiquitous in the crust of the Earth. Because of their high permeability, fractures usually provide the main pathways for fluid flow and control fluid migration in geological systems (Igonin et al., 2021). When the flowing fluid is reactive, the dissolution of minerals within fracture walls would expand the fracture aperture and form distinct dissolution patterns. These dissolution patterns determine how the dissolved region develops and how the permeability increases (Roded et al., 2018;Wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…2021; Wang et al. 2022). Specifically, when a salt is dissolving in a liquid, dynamic mass transport phenomena around the dissolving solid exist, changing the shape of the solid body of the salt.…”
Section: Introductionsupporting
confidence: 55%
“…2021; Wang et al. 2022). Specifically, when a salt is dissolving in a liquid, dynamic mass transport phenomena around the dissolving solid exist, changing the shape of the solid body of the salt.…”
Section: Introductionsupporting
confidence: 55%
“…When the advection and reaction rates are comparable, the wormhole pattern emerges, and the permeability increases significantly. A large number of studies have indicated how the key factors, including flow rate (Detwiler et al., 2003; Starchenko et al., 2016; Szymczak & Ladd, 2009; Upadhyay et al., 2015; Wang et al., 2022; Xu et al., 2020), fluid reactivity (Deng et al., 2020), multiple fluids (Jiménez‐Martínez et al., 2020; Ott & Oedai, 2015), initial geometry (Cheung & Rajaram, 2002; Hanna & Rajaram, 1998), mineral heterogeneity (Al‐Khulaifi et al., 2017; Deng et al., 2017; You & Lee, 2022), and stress conditions (Roded et al., 2018; Spokas et al., 2018), affect the dissolution patterns. However, the role of gravity in dissolution dynamics is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Under a no‐external‐flowing condition, experimental and numerical studies showed that in a horizontal configuration, the buoyancy‐driven convection reproduces beautiful patterns like scallops, grooves, and rillenkarren on the upper surface (Cohen et al., 2020; Favier et al., 2019; Sullivan et al., 1996; Thomas & Armistead, 1968). Under a flowing condition, the interplay between buoyancy‐driven convection and forced convection would generate parallel grooves channels along the bulk flow direction (Wang et al., 2022) and significantly affect the local dissolution rate. Induced by this interplay, an interesting phenomenon, namely dissolution hotspot (Hu et al., 2021), has been recently observed and quantified in radial horizontal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Characterized by the Péclet number and Damköhler number, the dissolution of rough fracture at the system scale leads to different dissolution patterns. Generally, as the flow rate increases, the dissolution patterns in rough fractures shift from compact to wormhole (channeling) and further to uniform patterns (Deng, Steefel, et al., 2018; Detwiler & Rajaram, 2007; Elkhoury et al., 2013; Hu et al., 2021; Starchenko & Ladd, 2018; Szymczak & Ladd, 2009; Wang et al., 2022). For most of the core flooding experiments mentioned above, the evolution of fracture morphologies is usually quantified by the change in fracture aperture, namely the distance between the upper and lower rough surfaces (Detwiler & Rajaram, 2007; Detwiler et al., 2003; Szymczak & Ladd, 2012; Wang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of channels is obtained from the selected profiles of the natural rock surfaces. Although the dissolution process of single‐crystal channels lacks the geochemical reactions and mineral heterogeneity compared to the reaction in geologic systems, the coupled effect of reaction, diffusion, and convection in channels, a core issue in fluid‐rock interaction studies, can be well represented by flow cells fabricated with single‐mineral crystal (Detwiler et al., 2003; Golfier et al., 2002; Song et al., 2014; Wang et al., 2022). Furthermore, the homogeneity of NaCl crystals facilitates our focus on the effect of surface roughness on the dissolution process.…”
Section: Introductionmentioning
confidence: 99%